LEISURE IN PSYCHOLOGY AND ISLAM: COMPARATIVE STUDIES - Karimulloh, Karimulloh; Grasiaswaty, Novika; Linda Siregar, Mustika Ema (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Islam is a exhaustive religion that talks about many facets of daily life, including recreational or leisure activities. Since leisure research has always been regarded primarily through the lens of Western psychology theory, it has grown significantly in Europe and America. There hasn't been any more research done on the benefits of leisure activity participation from an Islamic perspective. This study tries to compare leisure from the viewpoints of psychology and Islam. Comparative research is conducted by reading and analysing carefully from a variety of pertinent sources, including those from Islam and psychology. The findings indicated that psychology and Islam encourage leisure activities that are beneficial for addressing psychological, educational, social, self-relaxation, and physiological demands. While Islam dictates that one's leisure time activities do not contradict with Islamic beliefs in order to create happy people in this world and the hereafter, psychology is more open in many areas.